1995
DOI: 10.1002/j.1550-8528.1995.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Drugs That Cause Weight Gain

Abstract: Among drugs which cause weight gain, the tricyclic antidepressant medications are a drug class producing persistent andproblematic bodyweight gaininmanytreated patients. Major depressive illness is often associated with reductions in appetiteandbodyweight,andtreatmentwith antidepressants effectively restores mood,appetite andweight. However, afrequent complaint of patients treated with tricyclic drugs is of excessive and unwanted weight gain, oftentimes resulting in medication noncompliance. The incidence of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…Several classes of psychotropic medications are associated with unwanted weight gain, including antipsychotics, antidepressants, mood stabilizers, and, to a lesser degree, anxiolytics (68)(69)(70). Weight gain could theoretically be due to increased energy intake, decreased energy expenditure, or a combination of the two; in most cases, we have too little information to distinguish among these possibilities.…”
Section: Do Psychotropic Medications Play a Role In Obesity?mentioning
confidence: 99%
See 3 more Smart Citations
“…Several classes of psychotropic medications are associated with unwanted weight gain, including antipsychotics, antidepressants, mood stabilizers, and, to a lesser degree, anxiolytics (68)(69)(70). Weight gain could theoretically be due to increased energy intake, decreased energy expenditure, or a combination of the two; in most cases, we have too little information to distinguish among these possibilities.…”
Section: Do Psychotropic Medications Play a Role In Obesity?mentioning
confidence: 99%
“…However, as reviewed by Ackerman and Nolan (68), more recent studies have reported relatively modest mean weight gains, even over the long term, and much larger increases in a relatively small number of patients. Of the tricyclics, amitriptyline is thought to induce the most weight gain (67,69). The mechanism of tricyclic antidepressant-induced weight gain appears to involve decreased basal metabolic energy expenditure and diet-induced thermogenesis.…”
Section: Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Body weight at one age is strongly correlated with body weight decades later, which suggests a strong genetic influence on body weight. 2,3 However, the genotypical body weight development depends upon environmental influences such as lifestyle, 4,5 and various life events, for example, illness, 6 long-term medication 7 and pregnancy, 8 can alter the genetically programmed weight development trajectory.…”
Section: Introductionmentioning
confidence: 99%